2015
DOI: 10.1007/s00415-015-7716-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolated, subtle, neurological abnormalities in neurologically and cognitively healthy aging subjects

Abstract: The aim of this study is to describe the frequency of isolated, subtle, neurological abnormalities (ISNAs) in a large population of neurologically and cognitively healthy subjects and to compare ISNAs to various types of MRI-detected cerebrovascular lesions and subcortical brain atrophy in different age classes. 907 subjects were selected from a large, prospective hospital-based study. At baseline neurological examination, 17 ISNAs were selected. Primitive reflexes were the most common ISNAs (35.8 %), while dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 61 publications
(58 reference statements)
0
27
0
Order By: Relevance
“…Details of the inclusion and exclusion criteria of the CogItA study have been reported elsewhere. 20 Informed consent was obtained from all participants and relatives. The study was approved by the University Hospital ethics committee and complies with the declaration of Helsinki.…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…Details of the inclusion and exclusion criteria of the CogItA study have been reported elsewhere. 20 Informed consent was obtained from all participants and relatives. The study was approved by the University Hospital ethics committee and complies with the declaration of Helsinki.…”
Section: Participantsmentioning
confidence: 99%
“…Many vascular risk factors (VRFs) and vascular diseases (VDs) were considered and assessed as reported elsewhere. 20,29 Since multiple VRFs and VDs often coexist, we created the VRF and VD summary scores indicating for each participant the sum of the individual VRFs and VDs that were concurrently present. APOE genotypes were determined by using standard methods.…”
Section: Baseline Clinical Assessmentmentioning
confidence: 99%
See 3 more Smart Citations